Pengawalan dan Pendampingan Usaha Mikro dalam Penyusunan Laporan Keuangan Sederhana sebagai Dasar Pengambilan Keputusan Bisnis - Kurniawan Kurniawan; Amrizal Salida; Asrini Asrini; Haeril Haeril; Fadlina Fadlina (Jurnal Akademik Pengabdian Masyarakat Ichsan Sidrap, 2025)
Micro-enterprises play a strategic role in regional economic growth and community empowerment. However, many micro-entrepreneurs still lack the knowledge and skills to prepare simple and structured financial reports. This shortcoming results in poor business management, inaccurate business decision-making, and difficulties in accessing financing from formal financial institutions. This community service activity aims to provide assistance and mentoring to five selected micro-enterprises in Pangkajenne City, Sidenreng Rappang Regency, in preparing simple financial statements as a foundation for making business decisions. The methods used include partner identification, needs assessment, basic financial report training, and individual mentoring through an on-site coaching approach. The results show a significant improvement in the financial literacy of the partners, the development of better financial recording habits, and the initial ability to independently prepare simple financial statements. Moreover, this activity supports the partners' readiness to access financing and plan business development strategies. This program demonstrates that structured academic intervention can have a real impact in strengthening the capacity of micro-enterprises in a sustainable way.